A photometric analysis of seventeen binary stars using speckle imaging - Davidson Jr., J.W.; Baptista, B.J.; Horch, E.P.; Franz, O.; Van Altena, W.F. (Astronomical Journal, 2009)
Magnitude differences obtained from speckle imaging are used in combination with other data in the literature to place the components of binary star systems on the H-R diagram. Isochrones are compared with the positions obtained, and a best-fit isochrone is determined for each system, yielding both masses of the components as well as an age range consistent with the system parameters. Seventeen systems are studied, 12 of which were observed with the 0.6 m Lowell-Tololo Telescope at Cerro Tololo Inter-American Observatory and six of which were observed with the WIYN 3.5 m Telescope (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories) at Kitt Peak. One system was observed from both sites. In comparing photometric masses to mass information from orbit determinations, we find that the photometric masses agree very well with the dynamical masses, and are generally more precise. For three systems, no dynamical masses exist at present, and therefore the photometrically determined values are the first mass estimates derived for these components. © 2009 The American Astronomical Society. All rights reserved.
Keywords: Binaries: visual techniques; High angular resolution techniques; Interferometric techniques; Photometric; dept.phy; peer-reviewed

Binary and multiple stars - Horch, E. (Astrometry for astrophysics: Methods, Models, and Applications, 2009)
Introduction Two or more stars that are located close together in space interact gravitationally, causing deviations from linear motion as each star is accelerated. If we consider the case of two stars with a physical separation of many times the radius of either star (but still close enough to generate significant accelerations), it is sufficient to consider the stars as point masses. The equations of motion for such a system can be solved by assuming the inverse-square law of gravity and applying Newton's laws of motion. Newton's solution elegantly explained Kepler's laws of planetary motion, since one of the general solutions of motion is an ellipse with the more massive body (the Sun, in the case of the Solar System) at one focus. Kepler's third law of planetary motion (i.e. the harmonic law) as applied to the binary-star situation can be written where m1 and m2 are the masses of the two stars in solar units, a is the semi-major axis of the relative orbital ellipse in astronomical units, and P is the orbital period of the system in years. If you can only apply this formula, then it is not possible to obtain individual masses from the observables on the right-hand side, nor is the mass sum possible without an estimate of the parallax of the system (which allows for the conversion of a from an angular measure to astronomical units). Furthermore, while it is usually possible to measure the orbital period to high precision, the application of the formula is complicated by the fact that the semi-major axis, and implicitly the parallax, is raised to the third power. © Cambridge University Press 2013.
Keywords: dept.phy

Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed

Low loss EELS study of the ultrathin SrTiO3 film grown on the si single crystal - Su, Dong; Couillard, Martin; Sawicki, M; Broadbridge, Christine; Zhu, Y. (Microscopy and Microanalysis, 2009)
Keywords: dept.phy

Comparing the force and motion conceptual evaluation and the force concept inventory - Thornton, Ronald K.; Kuhl, Dennis; Cummings, Karen; Marx, Jeffrey (Physical Review Special Topics-Physics Education Research, 2009)
In this paper we compare and contrast student's pretest/post-test performance on the Halloun-Hestenes force concept inventory (FCI) to the Thornton-Sokoloff force and motion conceptual evaluation (FMCE). Both tests are multiple-choice assessment instruments whose results are used to characterize how well a first term, introductory physics course promotes conceptual understanding. However, the two exams have slightly different content domains, as well as different representational formats; hence, one exam or the other might better fit the interests of a given instructor or researcher. To begin the comparison, we outline how to determine a single-number score for the FMCE and present ranges of normalized gains on this exam. We then compare scores on the FCI and the FMCE for approximately 2000 students enrolled in the Studio Physics course at Rensselaer Polytechnic Institute over a period of eight years (1998-2006) that encompassed significant evolution of the course and many different instructors. We found that the mean score on the FCI is significantly higher than the mean score on the FMCE, however there is a very strong relationship between scores on the two exams. The slope of a best fit line drawn through FCI versus FMCE data is approximately 0.54, and the correlation coefficient is approximately r=0.78, for preinstructional and postinstructional testings combined. In spite of this strong relationship, the assessments measure different normalized gains under identical circumstances. Additionally, students who scored well on one exam did not necessarily score well on the other. We use this discrepancy to uncover some subtle, but important, differences between the exams. We also present ranges of normalized gains for the FMCE in a variety of instructional settings.
Keywords: dept.phy

Observations of binary stars with the differential speckle survey instrument. i. instrument description and first results - Horch, Elliott P.; Veillette, Daniel R.; Gallé, Roberto Baena; Shah, Sagar C.; O'Rielly, Grant; van Altena, William F. (The Astronomical Journal, 2009)
First results of a new speckle imaging system, the Differential Speckle Survey Instrument, are reported. The instrument is designed to take speckle data in two filters simultaneously with two independent CCD imagers. This feature results in three advantages over other speckle cameras: (1) twice as many frames can be obtained in the same observation time which can increase the signal-to-noise ratio for astrometric measurements, (2) component colors can be derived from a single observation, and (3) the two colors give substantial leverage over atmospheric dispersion, allowing for subdiffraction-limited separations to be measured reliably. Fifty-four observations are reported from the first use of the instrument at the Wisconsin-Indiana-Yale-NOAO 3.5 m Telescope9The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories. in 2008 September, including seven components resolved for the first time. These observations are used to judge the basic capabilities of the instrument. © 2009. The American Astronomical Society. All rights reserved.
Keywords: astrometry; binaries: close; binaries: visual; dept.phy; instrumentation: high angular resolution; instrumentation: interferometers; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Research grade instrumentation for nanotechnology and MSE education - Broadbridge, Christine; Garofano, Jacquelynn; Altman, Eric I; Khalil, Yehia F; Henrich, Victor E; Segal, Y; Padmore, Myrtlerose; Michael, Philip; Walker, Fred (2009)
The Center for Research on Interface Structures and Phenomena (CRISP) is a National Science Foundation (NSF) Materials Research Science and Engineering Center (MRSEC). CRISP is a partnership between Yale University, Southern Connecticut State University (SCSU) and Brookhaven National Laboratory. A main focus of CRISP research is complex oxide interfaces that are prepared using epitaxial techniques, including molecular beam epitaxy (MBE). Complex oxides exhibit a wealth of electronic, magnetic and chemical behaviors, and the surfaces and interfaces of complex oxides can have properties that differ substantially from those of the corresponding bulk materials. CRISP employs this research program in a concerted way to educate students at all levels. CRISP has constructed a robust MBE apparatus specifically designed for safe and productive use by undergraduates. Students can grow their own samples and then characterize them with facilities at both Yale and SCSU, providing a complete research and educational experience. This paper will focus on the implementation of the CRISP Teaching MBE facility and its use in the study of the synthesis and properties of the crystalline oxide-silicon interface. C 2010 Materials Research Society.
Keywords: Brookhaven national laboratory; Bulk materials; Chemical behavior; Complex oxides; Crystal growth; Crystalline materials; Crystalline oxides; Educational experiences; Epitaxial techniques; Interface structures; Materials research; Materials research societies; Materials science; Molecular beam epitaxy; Molecular beams; National Science Foundations; Research; Research programs; Science and engineering; Silicon interface; Students; Surfaces and interfaces; Yale University; dept.phy

Authentic science research and the utilization of nanoscience in the non-traditional classroom setting - Day, Deborah A; Yu, Zizi; Wang, Zelun; Dalecki, Jennifer; Jadbabaie, Arian; Feng, Emily Z; Mattessich, Thomas J; Caragianis-Broadbridge, Christine; Reed, Mark A; Munden, Ryan (2009)
Applications of nanoscience in the non-traditional classroom have successfully exposed students to various methods of research with applications to micro- and nano-electronics. Activities obtained from the NanoSense website associated with current global energy and water concerns are solid examples 1. In this regard, all 36 students in the 2008-2009 Science Research Program (SRP) prepared and delivered individual and group lesson plans in addition to their authentic, year-long research projects. Two out of 36 students selected nanoscience based projects in preparation for science fair competition in 2009. Additionally, preliminary research was conducted while participating in the Center for Research on Interface Structures and Phenomena (CRISP) Research Experience for Teachers (RET) Program in summer 2008 which supported the idea of developing a photolithography kit. This kit is intended to introduce high school students to the fundamentals of photolithography. In this paper, the design, implementation and feasibility of this kit in the high school classroom is described as well as details involving individual and group nanoscience based projects. Supporting educational models include self-regulated learning (SRL) concepts: situated cognition; social constructivism; Renzulli's (1977) enrichment triad and Types I - III inquiry enrichment activities 2,3. © 2009 Materials Research Society.
Keywords: Classroom settings; Education computing; Educational models; Global energy; High school; High school students; Interface structures; Lesson plans; Micro- and nano-electronics; Nanoscience; Non-traditional; Photolithography; Research; Research experience; School buildings; Science fairs; Science research; Self-regulated learning; Situated cognition; Social constructivism; Students; Teaching; dept.phy

Computer assisted analysis of microscopy images - Sawicki, M; Munhutu, P; Daponte, John S; Caragianisbroadbridge, Christine; Lehman, Ann; Sadowski, Thomas; Garcia, E; Heyden, C; Mirabelle, L; Benjamin, P (2009)
The use of Transmission Electron Microscopy (TEM) to characterize the microstructure of a material continues to grow in importance as technological advancements become increasingly more dependent on nanotechnology 1. Since nanoparticle properties such as size (diameter) and size distribution are often important in determining potential applications, a particle analysis is often performed on TEM images. Traditionally done manually, this has the potential to be labor intensive, time consuming, and subjective 2. To resolve these issues, automated particle analysis routines are becoming more widely accepted within the community 3. When using such programs, it is important to compare their performance, in terms of functionality and cost. The primary goal of this study was to apply one such software package, ImageJ to grayscale TEM images of nanoparticles with known size. A secondary goal was to compare this popular open-source general purpose image processing program to two commercial software packages. After a brief investigation of performance and price, ImageJ was identified as the software best suited for the particle analysis conducted in the study. While many ImageJ functions were used, the ability to break agglomerations that occur in specimen preparation into separate particles using a watershed algorithm was particularly helpful 4. © 2009 SPIE-IS&T.
Keywords: Agglomeration; Commercial softwares; Computer aided analysis; Computer-assisted analysis; Data visualization; Electron microscopes; General purpose; Gray-scale; Image processing; Imaging systems; Labor intensives; Microscopy; Microscopy images; Nanoparticles; Open sources; Particle analysis; Particle size analysis; Potential applications; Semiconductor quantum wires; Software packages; Specimen preparation; TEM images; Technological advancements; Tem; Thresholding; Transmission Electron Microscope (TEM); Transmission electron microscopy; Visualization; Water-shed algorithms; dept.csc; dept.phy